Collective learning for resilience in Global South cities: a community-based systems mapping approach to integrated climate and health action - Morais, Lidia Maria de Oliveira; Borde, Elis; Tatah, Lambed; Thondoo, Meelan; Wayas, Feyisayo A.; Gordon-Strachan, Georgiana; Obonyo, Charles; Assah, Felix; Oni, Tolu; Caiaffa, Waleska Teixeira; Garcia, Leandro (Frontiers in Public Health, 2025)
IntroductionCities in the Global South face escalating climate change challenges, including extreme weather events that disproportionately affect marginalized populations and exacerbate health risks, such as non-communicable diseases (NCDs). Climate resilience, defined as the capacity to adapt and recover from climate-related events, requires intersectoral collaboration between governments and civil society.MethodsThis study employs a Community-based System Dynamics approach, leveraging shared learning across four cities—Belo Horizonte (BH, Brazil), Yaoundé (Cameroon), Kingston (Jamaica), and Kisumu (Kenya)—through the Global Diet and Activity Research Network (GDAR). An implementation of the method in BH is detailed, examining drivers and interdependencies shaping community-based climate resilience strategies against heavy rainfalls.ResultsIn BH, findings highlight the interplay between urbanization risks, vulnerabilities, heavy rainfall, and NCDs, with visibility, resources, education, and training identified as critical intervention points.ConclusionThis study underscores the importance of aligning community action with public policy and highlights opportunities for collective learning and resilience-building for climate change in Global South cities.